Solve and check result: 5t − 3 = 3t − 5

Advertisement Remove all ads

#### Solution

5t − 3 = 3t − 5

On transposing 3t to L.H.S and −3 to R.H.S, we obtain

5t − 3t = −5 − (−3)

2t = −2

On dividing both sides by 2, we obtain

t = −1

L.H.S = 5t − 3 = 5 × (−1) − 3 = −8

R.H.S = 3t − 5 = 3 × (−1) − 5 = − 3 − 5 = − 8

L.H.S. = R.H.S.

Hence, the result obtained above is correct.

Concept: Solving Equations Having the Variable on Both Sides

Is there an error in this question or solution?

#### APPEARS IN

Advertisement Remove all ads